Faktor-Faktor Yang Mempengaruhi Sanitasi Pasar Wameo Di Kota Bau Bau Tahun 2020 - Nurfatmala (Unit Publikasi Ilmiah Perkumpulan Intelektual Madani Indonesia, 2021)
Human activities that occur in a market will result in environmental problems, such as market sanitation. To anticipate this, monitoring efforts need to be carried out on an ongoing basis so that buyers, sellers and market employees as well as the people who live can avoid the disruption of infectious diseases. This study aims to determine the factors that affect the sanitation of the Wameo market in Baubau City in 2020. This type of research is quantitative analytic which tries to explore and why this health phenomenon occurs, with a cross sectional design. The population in this study were 346 respondents. The sample in this study was 185 respondents, where the sample was taken by random sampling. The results of the chi-square statistical test on the effect of Trader Participation on Market Sanitation obtained the value of X2count = 8.988 (X2 table = 3.841), the value of = 0.004. Thus, X2 count is greater than X2 table or = 0.004 is smaller than = 0.05 then Ho is rejected and Ha is accepted, meaning that there is an influence between the participation of traders on the sanitation of the Wameo market in Baubau City in 2020. The value of X2count = 8.988 ( X2 table = 3.841), the value of = 0.028. Thus, X2 count is greater than X2 table or = 0.028 smaller than = 0.05, then Ho is rejected and Ha is accepted, meaning that there is an influence between the support of the janitor on the sanitation of the Wameo market. The conclusion in this study is that there is an effect of the participation of traders on the sanitation of the Wameo market in Baubau City in 2020.